A simulation and experiential learning intervention for labor and delivery providers to address HIV stigma during childbirth in Tanzania: study protocol for the evaluation of the MAMA intervention - Melissa H. Watt; Linda M. Minja; Mariam Barabara; Pendo Mlay; Maya J. Stephens; Gaudensia Olomi; Janeth Mlay; Virginie Marchand; Blandina T. Mmbaga; Olivia R. Hanson; Susanna R. Cohen (BMC, 2023)
Abstract Background The experience of HIV stigma during intrapartum care can impact women's trust in the health care system and undermine their long-term commitment to HIV care engagement. Delivery of respectful maternity care (RMC) to women living with HIV (WLHIV) can improve quality of life and clinical outcomes. The goal of this study is to conduct an evaluation of MAMA (Mradi wa Afya ya Mama Mzazi, Project to Support the Health of Women Giving Birth), a simulation team-training curriculum for labor and delivery providers that addresses providers' instrumental and attitudinal stigma toward WLHIV and promotes the delivery of evidence-based RMC for WLHIV. Methods The MAMA intervention will be evaluated among healthcare providers across six clinics in the Kilimanjaro Region of Tanzania. To evaluate the impact of MAMA, we will enroll WLHIV who give birth in the facilities before (n = 103 WLHIV) and after (n = 103 WLHIV) the intervention. We will examine differences in the primary outcome (perceptions of RMC) and secondary outcomes (postpartum HIV care engagement; perceptions of HIV stigma in the facility; internal HIV stigma; clinical outcomes and evidence-based practices) between women enrolled in the two time periods. Will also assess participating providers (n = 60) at baseline, immediate post, 1-month post training, and 2-month post training. We will examine longitudinal changes in the primary outcome (practices of RMC) and secondary outcomes (stigma toward WLHIV; self-efficacy in delivery intrapartum care). Quality assurance data will be collected to assess intervention feasibility and acceptability. Discussion The implementation findings will be used to finalize the intervention for a train-the-trainer model that is scalable, and the outcomes data will be used to power a multi-site study to detect significant differences in HIV care engagement. Trial Registration The trial is registered at clinicaltrials.gov, NCT05271903.